Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 34004 species occurrences available in GBIF matching the query: { "and" : [ "Country is Nepal", "HasCoordinate is true", "BasisOfRecord is Specimen" ] } The dataset includes 34004 records from 155 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0099867-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences